2022
DOI: 10.3390/drones6110370
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Cover Estimation in Semi-Arid Shrublands after Prescribed Burning: Field-Ground and Drone Image Comparison

Abstract: The use of drones for vegetation monitoring allows the acquisition of large amounts of high spatial resolution data in a simple and fast way. In this study, we evaluated the accuracy of vegetation cover estimation by drones in Mediterranean semi-arid shrublands (Sierra de Filabres; Almería; southern Spain) after prescribed burns (2 years). We compared drone-based vegetation cover estimates with those based on traditional vegetation sampling in ninety-six 1 m2 plots. We explored how this accuracy varies in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Vegetation cover was estimated on a visual basis, determining the height and the surface covered by each vegetation strata in a 5 m radius centered on each trap [46]. Despite the fact that this method is time-consuming and subjective, it was suggested that it provides good concordance with modern objective methods for sampling vegetation [47]. We estimated the cover (surface occupied in %) of five variables: tree canopy, tall shrub (>1.5 m), short shrub (<1.5 m), herbaceous, and branch cover.…”
Section: Small Mammal Samplingmentioning
confidence: 99%
“…Vegetation cover was estimated on a visual basis, determining the height and the surface covered by each vegetation strata in a 5 m radius centered on each trap [46]. Despite the fact that this method is time-consuming and subjective, it was suggested that it provides good concordance with modern objective methods for sampling vegetation [47]. We estimated the cover (surface occupied in %) of five variables: tree canopy, tall shrub (>1.5 m), short shrub (<1.5 m), herbaceous, and branch cover.…”
Section: Small Mammal Samplingmentioning
confidence: 99%